Rapid method for determining malondialdehyde as secondary oxidation product in palm olein system by Fourier transform infrared spectroscopy - Mirghani, Mohamed Elwathig Saeed; Che Man, Yakoob; Selamat, Jinap; Baharin , B. S.; Bakar, Jamilah (http://www.wiley.com/bw/journal.asp?ref=0958-0344, 2002)
A simple and rapid Fourier transform infrared (FTIR) spectroscopic method has been developed for the quantitative determination of malondialdehyde as secondary oxidation product in a palm olein system. The FTIR method was based on a sodium chloride transmission cell and utilised a partial least square statistical approach to derive a calibration model. The frequency region combinations that gave good calibration were 2900–2800, and 1800–1600 cm−1. The precision and accuracy, in the range 0–60 µmol malondialdehyde/kg oil, were comparable to those of the modified distillation method with a coefficient of determination (r2) of 0.9891 and standard error of calibration of 1.49. The calibration was cross-validated and produced an r2 of 0.9786 and standard error of prediction of 2.136. The results showed that the FTIR method is versatile, efficient and accurate, and suitable for routine quality control analysis with the result obtainable in about 2 min from a sample of less than 2 mL. Copyright © 2002 John Wiley & Sons, Ltd.